Multi-regional sequential pain syndrome - Yang, Xiao; Zhao, Kai-Jun; Liu, Jian-Min (Frontiers in Neurology, 2025)
ObjectiveTo report a novel clinical entity, “Multi-regional Sequential Pain Syndrome” (MRSPS), and evaluate the relationship between hypoperfusion, cryptogenic vertebral artery dissection (CVAD), and MRSPS.MethodsA 59-year-old female patient, with a chronic MRSPS condition spanning 10–30 years, underwent a comprehensive diagnostic evaluation including cranial CTA, MRI, DSA, and CT perfusion, culminating in the identification of CVAD via dynamic contrast-enhanced computed tomography (DCE-CT). The treatment strategy integrated repairing CVADs with stent implantation to address the hypoperfusion and MRSPS.ResultsFollowing intervention, hypoperfusion achieved complete improvement, and the patient achieved the complete resolution of pain and vertigo, with the modified Rankin Scale (mRS) score of 0 at the 1-year follow-up, signifying full neurological recovery.ConclusionCVADs, a key cause of brain tissue hypoperfusion in MRSPS, can be effectively treated by repair to alleviate the syndrome.